KEBANGKITAN MASJID KAMPUS DI YOGYAKARTA: EKSKLUSIF ATAU INKLUSIF? - AF. Djunaidi; Lukman A. Irfan; Edi Safitri (Millah: Journal of Religious Studies, 2016)
This research is motivated by the phenomenon of religious activities in mosques strengthening campus in Yogyakarta. The phenomenon of the strengthening of religious activity on campus is obviously very interesting to study. Moreover, the phenomenon has a tendency exclusive then the mosque likewise; The programs and activities actually mosque campus have a common goal that is about to present Islam in the middle of campus and community that was changing it shows the tendency that leads to what is known as “exclusivism of religion.” The subjects were four mosques campuses, namely the mosque at UGM, UNY, UII, and UIN Sunan Kalijaga. Methods of data collection in this study includes surveys, participatory observation, in-depth interviews (depth interview), and field notes. This study found that: Mosque campus has its own characteristics depending takmir or board mosque and activists. Tendency to exclusivity comes on board mosque. Then, the management of the campus mosque ideally an  early forerunner of the strengthening of religious movements. This religious movement to bring the interaction between activists intensified so through a process of internalization grow and shape the character.